Development and Characterization of an Endotoxemia Model in Zebra Fish - Hsu, Alan Y.; Gurol, Theodore; Sobreira, Tiago J. P.; Zhang, Sheng; Moore, Natalie; Cai, Chufan; Zhang, Zhong-Yin; Deng, Qing (Frontiers in Immunology, 2018)
Endotoxemia is a condition in which endotoxins enter the blood stream and cause systemic and sometimes lethal inflammation. Zebrafish provides a genetically tractable model organism for studying innate immunity, with additional advantages in live imaging and drug discovery. However, a bona fide endotoxemia model has not been established in zebrafish. Here we have developed an acute endotoxemia model in zebrafish by injecting a single dose of LPS directly into the circulation. Hallmarks of human acute endotoxemia, including systemic inflammation, extensive tissue damage, circulation blockade, immune cell mobilization, and emergency hematopoiesis, were recapitulated in this model. Knocking out the adaptor protein MyD88 inhibited systemic inflammation and improved zebrafish survival. In addition, similar alternations of pathways with human acute endotoxemia were detected using global proteomic profiling and MetaCore™ pathway enrichment analysis. Furthermore, treating zebrafish with a protein tyrosine phosphatase, non-receptor type 11 (SHP2) inhibitor decreased systemic inflammation, immune mobilization, tissue damage, and improved survival in the endotoxemia model. Together, we have established and characterized the phenotypic and gene expression changes of a zebrafish endotoxemia model, which is amenable to genetic and pharmacological discoveries that can ultimately lead to a better mechanistic understanding of the dynamics and interplay of the innate immune system.